The distribution of Uranotaenia Sapphirina and UR. socialis in Tabasco, Southern Mexico - Ortega Morales, Aldo I.; Garza Hernandez, Javier Alfonso; Rodríguez Martínez, Luis M.; Méndez Alvarado, William; López Hernández, Isaias; Medrano Santillana, Miguel; González Acosta, Cassandra; Correa Morales, Fabián (2022)
In Mexico, the genus Uranotaenia includes 11 species distributed mainly in the tropical and subtropical regions in the southeast of the country. Uranotaenia sapphirina has been reported in 18 states in Mexico: Campeche, Coahuila, Colima, Chiapas, Guerrero, Hidalgo, Jalisco, Mexico City, Mexico State, Michoaca´n, Morelos, Oaxaca, Quintana Roo, Sinaloa, Tabasco, Tamaulipas, Veracruz, and Yucata´n; whereas Ur. socialis has been reported in Chiapas and Quintana Roo. In recent surveillance studies of mosquito species in Tabasco, Ur. sapphirina and Ur. socialis were omitted due to the lack of recent collection records, but in historical records, the presence of Ur. sapphirina and one species consistent with the description of Ur. socialis were mentioned. During a mosquito survey collection, immature stages from ground-level natural habitats in conservation areas of Tabasco, Ur. sapphirina and Ur. socialis were collected in association with Anopheles albimanus, Culex erraticus, Mansonia titillans, and Ur. lowii. Additionally, 2 Mexican entomological collections were reviewed, searching additional records of those species. An identification key to separate larvae and adult females of Ur. sapphirina and Ur. socialis is provided. With the addition of Ur. sapphirina and Ur. socialis to the mosquito fauna of Tabasco, there are currently 107 species in the state, being the 3rd state in Mexico with the highest richness of mosquito species. Specimens collected during this study were deposited in the Collection of the Entomological and Bioassay Research Unit of Tabasco.